(untitled) (Research, Society and Development, 2022)
Objective: to present, from the scientific literature, the main difficulties faced by nurses in the management of the primary health care unit. Methodology: this is a narrative literature review carried out in SCIELO and LILACS data sources. The search took place in September 2021. The keywords used were “Nursing”, “Primary Health Care” and “Health Management”. The total of studies revealed in both data sources was 139 studies. After reading and analyzing the researched theoretical framework, 42 selected manuscripts were reached. However, after exhaustive reading of these articles, only nine (21.5%) manuscripts were included in the sample of the present research because they answered the guiding question of the study. Results: the sample of articles in the present study consisted of nine scientific articles. The difficulties most present in the routine and that make the work of this professional more difficult are lack of incentive and qualification and training courses, reduced professional staff, scarce human resources, work overload, lack of financial resources, lack of support from part of public management, and inadequate physical structures. Final Considerations: the difficulties faced by these professionals become a major challenge in the exercise of this profession, culminating directly in a precarious and unsafe quality of care for the patient.